Body composition assessment of English Premier League soccer players: a comparative DXA analysis of first team, U21 and U18 squads - Milsom, J.; Naughton, R.; O`Boyle, A.; Iqbal, Z.; Morgans, R.; Drust, B.; Morton, J. P. (Journal of Sports Sciences, 2015)
Professional soccer players from the first team (1st team, n = 27), under twenty-one (U21, n = 21) and under eighteen (U18, n = 35) squads of an English Premier League soccer team were assessed for whole body and regional estimates of body composition using dual-energy X-ray absorptiometry (DXA). Per cent body fat was lower in 1st team (10.0 ± 1.6) compared with both U21 (11.6 ± 2.5, P = 0.02) and U18 (11.4 ± 2.6, P = 0.01) players. However, this difference was not due to variations (P = 0.23) in fat mass between squads (7.8 ± 1.6 v 8.8 ± 2.1 v 8.2 ± 2.4 kg, respectively) but rather the presence of more lean mass in 1st team (66.9 ± 7.1 kg, P < 0.01) and U21 (64.6 ± 6.5 kg, P = 0.02) compared with U18 (60.6 ± 6.3 kg) players. Accordingly, fat mass index was not different (P = 0.138) between squads, whereas lean mass index was greater (P < 0.01) in 1st team players (20.0 ± 1.1 kg · m-2) compared with U18 players (18.8 ± 1.4 kg · m-2). Differences in lean mass were also reflective of higher lean tissue mass in all regions, for example, upper limbs/lower limbs and trunk. Data suggest that training and nutritional interventions for younger players